Ion beam-assisted solid phase epitaxy of SiGe and its application for analog memristors - Kim, Keonhee; Kang, Dae Cheol; Jeong, Yeonjoo; Kim, Jaewook; Lee, Suyoun; Kwak, Joon Young; Park, Jongkil; Hwang, Gyu Weon; Lee, Kyeong-Seok; Ju, Byeong-Kwon; Park, Jong Keuk; Kim, Inho (Elsevier BV, 2021)
Low dimensional defects such as dislocation in single crystal Si are known to serve as a fast diffusion path of metal ions. Recently, many efforts have been made to employ dislocations in single crystal based oxide and silicon as reliable Ag filaments in CBRAM (Conductive Bridge Resistive Memory). In this study, we report the synthesis of the SiGe epitaxy thin films by an ion beam-assisted solid phase epitaxy process and its ap-plication for analog CBRAM memristors. The epitaxial SiGe thin films were produced by implanting Ge ions into a LPCVD a-Si film, followed by post annealing. We found that the interface oxide between a-Si and c-Si hinders facile epitaxy growth of a-Si. Thus, the ion implantation parameters were carefully adjusted to effectively remove the interface oxide and produce the epitaxy thin films of high quality. The low dimen-sional defects, identified to be a stacking fault by TEM observations, were observed to be densely located near the surface region of the SiGe epitaxy thin film. We fabricated the CBRAM devices by sandwiching the epitaxial Si thin films between an active metal electrode of Ag and a heavily doped Si wafer. We investigated the performances of the CBRAM devices and discuss the effect of the low dimensional defects on the switching behaviors of the devices. We found that the Ge implantation enables forming-free CBRAM op-eration and also provides reduced variations in set and reset voltages. Furthermore, we performed the feasibility study on the use of the epitaxial Si based CBRAM for artificial synapse for neuromorphic computing. (c) 2021 The Authors. Published by Elsevier B.V. CC_BY_NC_ND_4.0